MAPPING OF MOUTAIN AND FOOTHILL LANDSCAPES - Siddikov Rasuljon Uktamovich; Ergasheva Marjona Otabek qizi (American Journals, 2025)
This article analyzes the theoretical and practical aspects of mapping mountain and foothill landscapes. It examines the structure of landscapes, the natural and anthropogenic factors affecting them, as well as the significance of modern cartographic technologies.
Keywords: Landscape, cartography, mountain regions, foothill zones, GIS (Geographic Information System) technologies.